The Effect of Acute Aerobic Exercise and Training on Mitochondrial Biogenesis - Kolifa, Μυρσίνη; Mougios, Βασίλης (Inquiries in Physical Education and Sport, 2010)
It is well established that aerobic exercise and training lead to increased mitochondrial density and number (known as mitochondrial biogenesis) which consequently improves the oxidative capacity of muscle fibers. However, there is little experimental evidence regarding the molecular events that mediate this adaptation. As a result, and with the valuable contribution of technological development, there is a growing scientific interest in the effect of exercise on gene expression of mitochondrial proteins and the clarification of the signalling events and transcription factors which determine mitochondrial biogenesis. The available body of knowledge indicates that the mechanical stimulus of exercise is transported to the nucleus (where most mitochondrial genes are found) through the increased concentration of Ca2+ and the activation of Ca2+-dependent enzymes, as well as through the activation of AMP-dependent protein kinase as a result of energy imbalance. The increased production of reactive oxygen species is another putative signal path for mitochondrial biogenesis. The most important regulator of mitochondrial biogenesis is considered to be peroxisome proliferator-activated receptor gamma coactivator-1 (PGC-1). This, in turn, controls a series of transcription factors, including peroxisome proliferator-activated receptors (PPAR) and , nuclear respiratory factors 1 and 2, and mitochondrial transcription factor, TFAM. Acute aerobic exercise increases the levels of mRNA and protein of PGC-1 and transcription factors, with diversity regarding the magnitude and timing of their peaks. Continuing muscle biopsy sampling for 48 h after the end of exercise ensures a more reliable kinetic response. Aerobically trained subjects are characterized by increased levels of mRNA and protein of PGC-1 and PPARs. Finally, a remarkable finding is that highintensity interval cycling lasting 30 s and interval training of the same characteristics increase gene expression of PGC-1 and promote mitochondrial biogenesis as effectively as the continuous submaximal highvolume training.